2017
DOI: 10.1088/1478-3975/aa7acc
|View full text |Cite
|
Sign up to set email alerts
|

Topography on a subcellular scale modulates cellular adhesions and actin stress fiber dynamics in tumor associated fibroblasts

Abstract: Cells can sense and adapt to mechanical properties of their environment. The local geometry of the extracellular matrix, such as its topography, has been shown to modulate cell morphology, migration, and proliferation. Here we investigate the effect of micro/nanotopography on the morphology and cytoskeletal dynamics of human pancreatic tumor-associated fibroblast cells (TAFs). We use arrays of parallel nanoridges with variable spacings on a subcellular scale to investigate the response of TAFs to the topograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…Nevertheless, both cell types show clear, and quantitatively similar, actin dynamics in response to surface textures. Consistent with our prior results11,23 , we find that nanoridges lead to persistent streaks of actin that are not seen on flat surfaces.Optical flow enables the quantification of both the reproducible streaks of actin seen on nanoridged surfaces and the more chaotic actin waves seen on flat surfaces. The latter waves are typically much wider than guided actin waves.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, both cell types show clear, and quantitatively similar, actin dynamics in response to surface textures. Consistent with our prior results11,23 , we find that nanoridges lead to persistent streaks of actin that are not seen on flat surfaces.Optical flow enables the quantification of both the reproducible streaks of actin seen on nanoridged surfaces and the more chaotic actin waves seen on flat surfaces. The latter waves are typically much wider than guided actin waves.…”
supporting
confidence: 91%
“…Previous studies of Dictyostelium discodium 11,12 , B cells 9 , and tumor-associated fibroblasts 23 showed similarity in actin response to texture, which suggests that guidance of actin driven by texture There are multiple mechanisms by which cells may respond to local forces and geometry 25 , including sensing mechanisms that can respond to membrane curvature on a variety scales 26 . In some cases, sensing mechanisms may rely on the preferential formation of focal adhesions.…”
Section: Discussionmentioning
confidence: 96%
“…In line with the behavior observed on unidirectional grooved substrates, cells including mesenchymal stem cells (MSC) (Bashur et al, 2009;Subramony et al, 2013), endothelial cells (Whited and Rylander, 2014;, glioblastoma cells (Kievit et al, 2013), or astrocytoma cells (Vimal et al, 2016) adopt on aligned fibers an elongated, spindle-like morphology and align along the fiber direction. Accordingly, cells migrate in the direction of the fibers (Kievit et al, 2013;Lee et al, 2014), faster and longer distances compared to randomly oriented fibers (Lee et al, 2014;Mi et al, 2015;Azatov et al, 2017;Wang et al, 2017). Fibers alignment can also have a cell-type dependent effect on cell proliferation: while fibroblasts (Lee et al, 2017) or corneal epithelial cells show an increased proliferation on non-aligned fibers (Yan et al, 2012), keratocytes (Yan et al, 2012) and MSC proliferate more on aligned scaffolds (Subramony et al, 2013).…”
Section: Electrospun Fibrous Substratesmentioning
confidence: 99%
“…A large number of studies using grooved substrates have reported an alignment of FAs in the grating direction, especially for small submicrometric groove/ridge width that encompasses the lateral dimension of FAs (250-500 nm) (Ohara and Buck, 1979;den Braber et al, 1998;Teixeira et al, 2003Teixeira et al, , 2004Franco et al, 2011;Saito et al, 2014;Azatov et al, 2017;Ray et al, 2017; Figure 6). More precisely, FAs were seen to assemble and elongate either preferentially on ridges (Ohara and Buck, 1979;den Braber et al, 1998;Ferrari et al, 2010Ferrari et al, , 2011Franco et al, 2011;Azatov et al, 2017) or on both ridges and grooves (Ray et al, 2017;Tabdanov et al, 2018). In addition, scaling of FAs width with the size of the ridges have been reported (Teixeira et al, 2003;Saito et al, 2014;Ray et al, 2017; Figure 6).…”
Section: Focal Adhesionsmentioning
confidence: 99%
“…[11,12] Indeed, lamin A and C expression, indirectly attached to actin stress fibers, has also been shown to increase on stiffer materials. [6] Besides material stiffness, other factors such as material chemistry and topography have also been shown to influence focal adhesions, actin stress fibers and lamin A and C. [13][14][15] Yes-associated protein 1 (YAP1) is an important mechanosensitive co-transcription factor that translocates to the nucleus at higher cellular tension to transduce these mechanical changes in the cell to changes in gene expression. [16] On stiffer materials and with more cellular tension human mesenchymal stromal cells (hMSCs) show increased osteogenic differentiation, while softer materials and lower cellular tension enhance differentiation to chondro-and adipogenic lineages.…”
Section: Introductionmentioning
confidence: 99%